2001
DOI: 10.1182/blood.v98.8.2339
|View full text |Cite
|
Sign up to set email alerts
|

Changes in AIDS-related lymphoma since the era of highly active antiretroviral therapy

Abstract: HIV infection is associated with a high incidence of AIDS-related lymphomas (ARLs). Since the use of highly active antiretroviral therapy (HAART), the incidence of AIDS-defining illnesses has decreased, leading to a significant improvement in survival of HIV-infected patients. The consequences of HAART use on ARL are under debate. This study compared the incidence and the characteristics of ARL before and after the use of HAART in a large population of HIV-infected patients in the French Hospital Database on H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
204
0
7

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(218 citation statements)
references
References 25 publications
7
204
0
7
Order By: Relevance
“…This suggests that cellular immune responses, compromised in AIDS, but recovering after HAART, could be important in the control of KSHV infection and in the development of KS. This is further supported by the observation that posttransplant KS lesions regress when immunosuppressive treatment is stopped (14)(15)(16)(17).…”
Section: Kshv and Antiviral Therapiesmentioning
confidence: 68%
“…This suggests that cellular immune responses, compromised in AIDS, but recovering after HAART, could be important in the control of KSHV infection and in the development of KS. This is further supported by the observation that posttransplant KS lesions regress when immunosuppressive treatment is stopped (14)(15)(16)(17).…”
Section: Kshv and Antiviral Therapiesmentioning
confidence: 68%
“…[20][21][22] With the advent of highly active antiretroviral therapy, the incidence of AIDSrelated non-Hodgkin's lymphomas has declined. [23][24][25] A meta-analysis of 23 cohort studies (involving 47 936 seropositive individuals) showed reduced incidence rates from 1992-1996 (6.2 per 1000 person-years) to 1997-1999 (3.6 per 1000 personyears). 23 Part of this reduction may be due to improved CD4 cell counts.…”
Section: Aids and Non-aids Diffuse Large B-cell Lymphoma R Madan Et Almentioning
confidence: 99%
“…24 Despite the three-fold increase in survival of patients with AIDS-related lymphomas, the prognosis still appears worse than HIV-negative patients with comparable disease. 24,26,27 It is unclear whether these differences between AIDS-related and non-AIDS diffuse large B-cell lymphomas reflect biological variations in the lymphoma itself, or in the immunodeficient host, or in both. A definitive understanding of the pathogenesis of AIDS-related diffuse large B-cell lymphomas is still lacking.…”
Section: Aids and Non-aids Diffuse Large B-cell Lymphoma R Madan Et Almentioning
confidence: 99%
“…2 NHL occurs at a greatly increased frequency in HIV-infected populations and despite a reduction in its incidence during the HAART era, it remains the second commonest AIDS defining malignancy after Kaposi's sarcoma. [3][4][5][6][7] Many of the 200 million individuals infected with HCV and the 50 million individuals infected with HIV are co-infected with both viruses. [8][9][10] As well as shared routes of transmission, there are many interactions between these small RNA viruses in which infection is often characterised by parenteral transmission followed by a seroconversion illness and then a long latent period lasting many years.…”
mentioning
confidence: 99%